2010
DOI: 10.1007/s11200-010-0007-9
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle-derived emissions and pollution on the road autovia 2 investigated by rock-magnetic parameters: A case study from Argentina

Abstract: In this work, we carried out a preliminary study of traffic-derived pollutants from primary sources (vehicles), and on roads (paved area), road borders and surroundings areas. The study is focussed on the identification, distribution and concentration of pollutants and magnetic carriers. Magnetic parameters and their analyses suggest that the magnetic signal of vehicle-derived emissions is controlled by a magnetite-like phase. Magnetic grain size estimations reveal the presence of fine particles (0.1−5 μm) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 48 publications
2
16
1
Order By: Relevance
“…Several rock-magnetic measurements were done, including magnetic susceptibility (κ) and anhysteretic and isothermal remanent magnetisation (ARM and IRM). As detailed in Marié et al (2010), magnetic susceptibility measurements were carried out using a magnetic susceptibility meter (MS2, Bartington Instruments Ltd) connected to the MS2B dual frequency sensor (470 and 4700 Hz). ARM was imparted by superimposing a DC field of 90 μT to an AF of 100 mT, using a partial ARM (pARM) device attached to a shielded demagnetizer (Molspin Ltd).…”
Section: M E T H O D Smentioning
confidence: 99%
“…Several rock-magnetic measurements were done, including magnetic susceptibility (κ) and anhysteretic and isothermal remanent magnetisation (ARM and IRM). As detailed in Marié et al (2010), magnetic susceptibility measurements were carried out using a magnetic susceptibility meter (MS2, Bartington Instruments Ltd) connected to the MS2B dual frequency sensor (470 and 4700 Hz). ARM was imparted by superimposing a DC field of 90 μT to an AF of 100 mT, using a partial ARM (pARM) device attached to a shielded demagnetizer (Molspin Ltd).…”
Section: M E T H O D Smentioning
confidence: 99%
“…a A larger Fe-rich particle; b Irregular angular magnetic particle Muxworthy et al 2001;Matzka and Maher 1999) have confirmed that, in the absence of heavy industry, traffic pollution is the main source of magnetic particles in urban environment. The highest magnetic signals are found within a distance of 5-7 m from the center of the road (2-3 m from the edge of the asphalt surface) (Hoffmann et al 1999;Marie et al 2010;Zhang et al 2006). Therefore, the elevated concentrations of magnetic particles and heavy metals in the roadside topsoils should be predominately attributed to the emission from traffic activities.…”
Section: Mechanism Of Magnetic Enhancement In Roadside Topsoilsmentioning
confidence: 99%
“…Because simple, rapid, and non-destructive magnetic measurement technique can be applied on various environmental samples, it has been expected that magnetic measurement is applicable for assessing heavy metal pollution derived from traffic activities. Several studies have successfully tested the applicability of magnetic proxies in detecting roadside pollution (El-Hasan 2008;Gautam et al 2005;Hoffmann et al 1999;Maher et al 2008;Marie et al 2010;Prajapati et al 2006;Zhang et al 2006). Therefore, this method represents an inexpensive and indirect approach in detecting heavy metal contaminations from traffic activities.…”
Section: Introductionmentioning
confidence: 99%
“…Car emissions also contain a significant fraction of magnetic particles (Hunt et al 1984;Flanders 1994;Olson and Skogerboe 1975;Hoffmann et al 1999;Goddu et al 2004;Gautam et al 2005;Sagnotti et al 2006Sagnotti et al , 2009Bućko et al 2010Bućko et al , 2011Chaparro et al 2010;Marie et al 2010;Jordanova et al 2014). Such particles come from abrasion and corrosion processes affecting metal parts, brake linings, tires, and road surfaces.…”
Section: Introductionmentioning
confidence: 99%